Pengaruh Deskripsi Pekerjaan, Spesifikasi Pekerjaan Terhadap Kinerja Karyawan PT. Murfa Surya Mahardika - Dhilah Fhadilah; Tarsisus Kana; Simon Siamsa (Musamus University, Merauke Papua Indonesia., 2021)
This study aims to determine the effect of job descriptions and job specifications on employee performance at PT. Murfa Surya Mahardika Merauke Branch. The population in this study were all employees of PT. Murfa Surya Mahardika Branch Merauke, totaling 36 people. The sample in this study amounted to 36 people with the determination using the nonprobability sampling method. The research approach used is a quantitative approach and uses multiple linear regression analysis with SPSS version 23. From the results of multiple linear regression analysis that has been processed, the equation Y = 0.300 + 0.455 + 0.554) + e. From the results of hypothesis testing, namely the t test and F test, it shows that the variables of job description and job specifications have a significant effect partially or simultaneously on the performance of the employees of PT. Murfa Surya Mahardika Branch Merauke. This is evidenced by the tcount of Job Description (X1) 3,834> ttable 1,692 with a significant level of 0.001 <0.05 so that Ha is accepted H0 is rejected. The tcount value of Job Specifications (X2) 4.805 > ttable 1.692 with a significant level of 0.000 <0.05 so that Ha is accepted H0 is rejected. Then the value of Fcount 262,900> Ftable 3,28 with a significant level of 0,000 <0.05 so that Ha is accepted H0 is rejected. The value of R Square is 0.937, which means that all independent variables jointly affect the performance of the employees of PT. Murfa Surya Mahardika Branch Merauke amounted to 93.7% while the remaining 6.3% was influenced by other variables not examined in this study.